STUDY OF THE ENERGY POTENTIAL OF THE BARKS OF SPECIES OF THE GENUS Myrcia (REMUNOM, 2025)
This article aimed to estimate the energy potential of the barks of species of the genus Myrcia by analyzing their calorific value, as well as determining their immediate and elemental composition, with the prospect of use in energy cogeneration. Four main analyses were performed: elemental analysis, which quantifies the elements carbon, hydrogen and oxygen present in the sample; immediate analysis, which evaluates ash, moisture and volatile matter contents; and the calculation of the upper and lower calorific value (PCS, PCI), which reflects the energy potential of the material. In addition, the particle size characterization was performed using the ImageJ software to evaluate the particle size distribution of the biomass. The characterization of the sawdust of the cumate species showed ash of 1.89%, volatile matter of 72.54% and fixed carbon of 25.54%. The elemental composition consisted of 49.42% carbon, 6.04% hydrogen and 42.67% oxygen. By digital image analysis, the sawdust showed an average diameter of 1.96 mm and low sphericity. The PCS and PCI were close to 20 MJ/kg. The biomass of the cumate species studied demonstrated an energy potential similar to the Amazonian biomass of other species already used in combustion processes. Therefore, the biomass residues of these species can be used in the energy cogeneration process.